LEARNING CYCLE 5E BERBASIS BLENDED LEARNING SEBAGAI SOLUSI PENINGKATAN HASIL BELAJAR MATERI KONSEP REDOKS DI MASA PANDEMI COVID 19: Blended Learning - Winata, Anggun (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2022)
Redox involves several abstract concepts. This causes students to often experience difficulties and conceptual errors in understanding the concept. The integration of blended learning with the 5E learning cycle is one of the innovations in chemistry learning that can help students understand abstract chemical concepts. The integration of learning is called a learning cycle based on blended learning. This study aims to find out how to improve student learning outcomes for class X redox material at SMA N 1 Tuban with a learning cycle based on blended learning. This type of research is Classroom Action Research (CAR) conducted in two cycles. Each cycle consists of planning, implementing, observing and reflecting. The subjects in this study were students of class X MIPA-4 at SMA N 1 Tuban. The research instruments used were learning instruments (syllabus, lesson plans, and learning scenarios, and moodles) and measurement instruments (cognitive learning outcomes tests, observation sheets). Data analysis of the research results was carried out by analyzing student learning mastery. The results of this study concluded that a blended learning-based learning cycle can improve student learning outcomes on redox for class X SMA N 1 Tuban. This can be seen from the learning outcomes in the realm of knowledge, attitudes and skills. learning outcomes in the realm of knowledge showed an increase from pre-cycle, cycle I and cycle II. The learning outcomes of the pre-cycle, first-cycle, and second-cycle knowledge domains were 61.91, 74.74, and 84.09, respectively. Mastery learning also increased from pre-cycle, cycle I, and cycle II, namely 12.50%, 62.50% and 90.63%. The learning outcomes of the attitude domain gave an increase from cycle I to cycle II, namely 66.63 to 67.13. The learning outcomes of the skill domain gave an increase from cycle I to cycle II, namely 73.91 to 74.39.